2019
DOI: 10.1002/gps.5071
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in prodromal dementia with Lewy bodies: Where do we stand?

Abstract: Objectives The aim of this review was to provide an overview of the literature on imaging in prodromal dementia with Lewy bodies (DLB). Design Systematic PubMed search and literature review. Results Diagnostic classification of the prodromal DLB stage remains to be established but is likely to require imaging biomarkers to improve diagnostic accuracy. In subjects with mild cognitive impairment with Lewy body disease (MCI‐LB) (here synonymous with prodromal DLB) and REM sleep behaviour disorder, a high risk con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…This finding supports the use of this ratio (or a visual rating scale assessment [26]) to identify those with more typical LB features. However, a recent review in MCI-LB [5] suggested that reduced posterior cingulate metabolism can occur in those who progress to DLB, and further work is needed to validate the use of posterior cingulate preservation as a predictor of LB disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding supports the use of this ratio (or a visual rating scale assessment [26]) to identify those with more typical LB features. However, a recent review in MCI-LB [5] suggested that reduced posterior cingulate metabolism can occur in those who progress to DLB, and further work is needed to validate the use of posterior cingulate preservation as a predictor of LB disease.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging of brain metabolism, either through FDG-PET, perfusion SPECT or arterial spin labelled MRI (ASL) [2][3][4] is often done as part of the investigation in dementia patients. Studies with FDG-PET in MCI-LB have found a hypometabolic pattern similar to that seen in dementia with Lewy bodies (DLB) [5], with parieto-occipital hypometabolism [6], and relative preservation of posterior cingulate (cingulate island sign) [7]. Compared with FDG-PET, ASL has the advantage of being cheaper, non-radioactive, and can be done alongside other MR imaging; Dolui [8] compared ASL and FDG in MCI-AD and age matched controls and found similarities between the two techniques, with the hypometabolism patterns in MCI-AD similar to those seen in AD dementia.…”
Section: Introductionmentioning
confidence: 90%
“…Another limitation is that a definite diagnosis based on a pathological evaluation is lacking. Further research with the addition of more cases and involving comparisons with other modalities, such as 123 I‐meta‐iodobenzylguanidine (MIBG) myocardial scintigraphy or 123 I‐Ioflupane SPECT is needed, particularly for an early diagnosis in the analysis of MCI patients …”
Section: Discussionmentioning
confidence: 99%
“…Various clinical symptoms, including olfactory dysfunction, dysautonomia, depression, and RBD, occur in patients with the prodromal state of DLB (before or at the onset of memory loss) (5)(6)(7)(8). Moreover, recent evidence suggests the existence of prodromal DLB characterized by PPA (9-11).…”
Section: Discussionmentioning
confidence: 99%
“…The core clinical features of DLB include visual hallucinations, fluctuating cognition, rapid eye movement sleep behavior disorders (RBD), and motor symptoms of parkinsonism, as well as cognitive impairment characterized by deficits of attention, executive function, and visual perception (4). Various clinical symptoms, including olfactory dysfunction, dysautonomia, depression, and RBD, are observed in patients with the prodromal state of DLB (before or at the onset of memory loss) (5)(6)(7)(8). Moreover, recent evidence suggests the occurrence of PPA in patients with prodromal DLB (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%